Regulating Water Companies - Klein, Michael; Irwin, Timothy (World Bank, Washington, DC, 2012)
The water industry differs in two key respects from such other network industries as gas, electricity, and telecommunications. First, it offers fewer opportunities for competition among suppliers, since the network of pipes accounts for a large part of the total cost of water and can be run efficiently only as a monopoly. Second, the quality of water is crucial but hard for consumers to check. So, to get the best performance out of water companies, governments need to regulate the price and quality of water. To do that job well, regulators must know the appropriate price. The authors explain that the best way to discover this price is to auction the right to supply water.